El papel de Memoria y la Educación en la formulación de la Juventud en la novela "El Camino" de Miguel Delibes (Journal of the College of Basic Education, 2022)
In this research we discuss consolidating the role of Memory and Education of the Younger Generations , specially the educated masses of students and academics through the support of the concepts in the meeting , it is considered a pillar of sacrifice and love for the homeland where it is rooted in the memory of man also use it , to serve the community and not be just a memory emotions and pathos it does nothing to serve the community and the country